An Optimized Robot-Based Technique for Cochlear Implantation to Reduce Array Insertion Trauma. (November 2018) - Torres, Renato; Jia, Huan; Drouillard, Mylène; Bensimon, Jean-Loup; Sterkers, Olivier; Ferrary, Evelyne; Nguyen, Yann
Objective: To compare the intracochlear trauma induced by optimized robot-based and manual techniques with a straight electrode array prototype inserted at different lengths. Study Design: Experimental study. Setting: Robot-based otologic surgery laboratory. Subjects and Methods: A prototype array was inserted at different insertion lengths (21 and 25 mm) in 20 temporal bones. The manual insertion was performed with a microforceps. The optimized approach consisted of an optimal axis insertion provided by a robot-based arm controlled by a tracking system, with a constant speed of insertion (0.25 mm/s) achieved by a motorized insertion tool. The electrode position was determined at the level of each electrode by stereomicroscopic cochlea section analysis. Results: A higher number of electrodes correctly located in the scala tympani was associated with the optimized approach ( P = .03, 2-way analysis of variance). Regardless of the insertion technique used, the array inserted at 25 mm allowed complete insertion of the active stimulating portion of the array in all cases. Insertion depth was greater when the array was inserted to 25 mm versus 21 mm ( P < .001, 2-way analysis of variance). The optimized insertion was associated with less trauma than that from manual insertion regardless the length of the inserted array ( P = .04, 2-way analysis of variance). Conclusion: Compared with a manual insertion, intracochlear trauma could be reduced with array insertion performed on an optimal axis by using motorized insertion and by applying a constant insertion speed.